Proceedings of the 22nd Conference of the Computer-Human Interaction Special Interest Group of Australia on Computer-Human Inte 2010
DOI: 10.1145/1952222.1952314
|View full text |Cite
|
Sign up to set email alerts
|

Communities of everyday practice and situated elderliness as an approach to co-design for senior interaction

Abstract: In the co-design project Senior Interaction a public care unit, university researchers, industrial partners, and senior citizens are working together to design living labs applying digital concepts that can strengthen social networks and interaction among seniors. When approaching people who we envisioned to be the future users we realized that almost nobody among the people between 55 and 75 years old identified themselves as 'elderly' or 'senior citizens', we realized that users are never just 'out there'. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 9 publications
0
47
0
Order By: Relevance
“…In fact a large proportion of older adults do not consider themselves "old"and live autonomously [43,44] and enjoy meaningful engagement with their families and their broader community [45]. Durick and colleagues reaffirm that older age does not necessarily entail being stagnant, isolated, a problem for society, and unhealthy or being incapable to learn new technology [25].…”
Section: Technologies For Older Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact a large proportion of older adults do not consider themselves "old"and live autonomously [43,44] and enjoy meaningful engagement with their families and their broader community [45]. Durick and colleagues reaffirm that older age does not necessarily entail being stagnant, isolated, a problem for society, and unhealthy or being incapable to learn new technology [25].…”
Section: Technologies For Older Usersmentioning
confidence: 99%
“…There's a need to look further into the subtlety and nuances of how routines and interactions are managed [54], how mundane arrangements are enacted [2], and how communities of practice are comprised [43] in seeking to design for independence, agency, and engagement. Considering the themes above could lead to successful design strategies to create IoT technologies that support the ageing population [4].…”
Section: Collecting and Interpreting Datamentioning
confidence: 99%
“…In addition, to our knowledge there is no work which affords empirical insights on related negotiation and decision processes in such broader real-life research settings. Besides reporting on challenges and obstacles linked to the need to permanently balance all stakeholders' visions, the paper deals with another aspect which is novel in Living Lab research: some researchers reported problems and strategies in the recruitment of suitable participants and on the impacts of their choice in the course of the project [4,31]. A design project located in a city quarter neighborhood is confronted with the situation to tackle a high diversity of possible future end-users, but will not be able to integrate every person in that shared living environment.…”
Section: Living Labsmentioning
confidence: 99%
“…to establish a shared thinking space of future possibilities (in a similar vein as e.g. described in [4]). Two essential features are the basis of the workshops: First, the delivery of off-the-shelf technology and support in individual and group-based appropriation, which is strongly linked to the individual's every-day life issues.…”
Section: Preparing the Elderly To Become Co-designersmentioning
confidence: 99%
See 1 more Smart Citation